Prevalence of Urinary Tract Infection and Antibiotic Susceptibility Pattern to Urinary Pathogens in Kathmandu Medical College and Teaching Hospital , Duwakot - Pradhan, Binita; Pradhan, SB (Birat Journal of Health Sciences, 2017)
Introduction In developing countries, urinary tract infections (UTIs) are one of the most commonly diagnosed diseases among the patient seeking medical service and being treated with empirical antibiotics which causes resistance. Objective To find out the prevalence of urinary tract infection and sensitivity pattern of antibiotics among bacterial pathogens isolated in patients attending Kathmandu Medical College Teaching Hospital, Duwakot. Methodology All the patients with the clinical suspicion of UTI were sent for urine culture. Prevalence of UTI and urinary pathogens isolated with antimicrobial profile was correlated. Result A total number of 1735 clinically suspected as UTI cases were sent for urine culture sensitivity. Total culture positive were 239 (13.8%). The majority of isolates were from female patients comprising 180 (75%). The most common pathogenic microorganism isolated was E.coli (79.1%). Second most common organism was Klebsiella (11.7%) followed by Citrobacter (3.34%) and Proteus (2.92%). The isolated microorganism showed maximum number of sensitivity with the antibiotics Ofloxacin and Ciprofloxacin. The isolated microorganism demonstrated resistance with Nalidixic Acid and Co-Trimoxazole. Conclusion Urinary tract infection is a commonly encountered case in general practice. Females are commonly affected than men. The microbiological profile and the antibiotic sensitivity pattern while initiating empirical treatment must be taken into account while planning for the management. Regular supervision of the sensitivity pattern of pathogenic microorganism is mandatory for effective treatment. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 134-137